1977. 60 letiyu oktyabrya udarnyy trud! - Rukavishnikov, V (Плакат СССР (Plakat), 1977)
Soviet agricultural worker holding sheaf of wheat among fields Original title: 1977. 60 летию октября ударный труд! PO-0662